Accuracy Improvement With Weight Mapping Strategy and Output Transformation for STT-MRAM-Based Computing-in-Memory - Xianggao Wang; Na Wei; Shifan Gao; Wenhao Wu; Yi Zhao (IEEE Journal on Exploratory Solid-State Computational Devices and Circuits)
This work presents an analog computing-in-memory (CiM) macro with spin-transfer torque magnetic random access memory (STT-MRAM) and 28-nm CMOS technology. The adopted CiM bitcell uses a differential scheme and balances the input resistance to minimize the nonideal factors during multiply-accumulate (MAC) operations. Specialized peripheral circuits were designed for the current-scheme CiM architecture. More importantly, strategies of accuracy improvement were innovatively proposed as follows: 1) mapping most significant bit (MSB) to the far side of the MRAM array and 2) output linear transformation based on the reference columns. Circuit-level simulation verified the functionality and performance improvement of the CiM macro based on the MNIST and CIFAR-10 datasets, realizing a 3% and 5% accuracy loss compared with the benchmark, respectively. The 640-GOPS (8 bit) throughput, 34.6-TOPS/mm2 area compactness, and 83.3-TOPS/W energy efficiency demonstrate the advantages of STT-MRAM CiM in the coming AI era.